THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE INCIDENT OF 7TH DAY POST PARTUM BLUES IN PUBLIC WOMEN AT BPS ASRI (Baturetno Subdistrict, Tuban District) - Qoyimah, Ilmiatus; Khoirotul Iftitakhiyyah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
In Indonesia, the incidence of post-partum blues is higher than the incidence in other countries in Asia. Postpartum blues is a problem that often occurs in postpartum mothers. Postpartum blues can be overcome by providing counseling to postpartum mothers. The research aimed to determine the relationship between family support and the incidence of postpartum blues on the 7th day in postpartum mothers in BPS Asri, Baturetno Village, Tuban District. This research uses a cross-sectional research method. The population in this study was all postpartum mothers who gave birth at BPS Asri in the last month, totaling 35 people. After applying the Simple Random Sampling method, 33 samples were obtained—a questionnaire sheet measuring tool. The results of this research were tested using the Spearman Rank test method using SPSS For Windows software, it was found that the p-value = 0.009 (α <0.05) which states that H1 is accepted, meaning there is a relationship between family support and the incidence of postpartum blues on the 7th day. Postpartum mother at BPS Asri, Baturetno Village, Tuban District. From the explanation above it can be concluded that family support can influence the incidence of postpartum blues, it is hoped that it can increase insight and knowledge so that it can emphasize the level of knowledge of family support